Global, regional and national disparities and temporal trends of common autoimmune disease burdens among children and adolescents from 1990 to 2019 - Chen Chen; Jing Guo; Fan Yang; Shan Zhang; Xiaohan Liu; Ning Huang; Paul Lodder; Mingyu Zhang (BMJ Global Health)
Introduction Previous evidence lacked a thorough review of the disparities of autoimmune diseases (AD) burdens among countries and regions, which led to an insufficient basis for developing country-specific developmental level relevant preventive measures. This study aimed to analyse disparities and trends of global, regional and national burden of common ADs in children and adolescents from 1990 to 2019 and to investigate the associations between specific ADs and varied country indexes.Methods All data for four major ADs were obtained from the Global Burden of Diseases Study 2019. Age period-cohort modelling was conducted to disentangle age, period and birth cohort effects on AD incidence from 1990 to 2019. Local regression smoothing models were used to fit the correlation between AD burdens and sociodemographic index (SDI). Pearson’s correlation was used to investigate varied country-level risk factors for disease burden.Results A global increase in four common ADs incidence was observed from 1.57 million to 1.63 million between 1990 and 2019 in the 0–24 age group. The age-standardised incidence rate of overall four ADs showed substantial regional and global variation with the highest incidence in high SDI regions. The age, period and cohort distributions of AD incidence varied significantly, especially in high SDI countries. Relative to the expected level of age-standardised incidence associated with SDI, the distribution varied by regions depending on the specific ADs. Countries with higher levels of socioeconomic development, better quality of life and easier access to healthcare and the healthcare system showed lower disease burdens of ADs.Conclusions The incidence patterns and disease burdens of ADs varied considerably according to age, time period and generational cohort, across the world between 1990 and 2019. Incidences of ADs in children and adolescents were significantly correlated with indexes involving risks of the environment, human rights and health safety and quality of life.